A taxonomic review of the Night Frog genus Nyctibatrachus Boulenger, 1882 in the Western Ghats, India (Anura: Nyctibatrachidae) with description of twelve new species - Biju, S. D.; Bocxlaer, Ines Van; Mahony, Stephen; Dinesh, K. P.; Radhakrishnan, C.; Zachariah, Anil; Giri, Varad; Bossuyt, Franky (Zootaxa, 2011)
A taxonomic revision of the genus Nyctibatrachus is presented. As a result, we recognize 27 species, 12 of which are new to science and described herein. Three ‘lost’ species—Nyctibatrachus sanctipalustris, Nyctibatrachus sylvaticus and Nannobatrachus kempholeyensis are rediscovered after their original descriptions and the latter two species are neotypified. Four species are lectotypified (Nannobatrachus beddomii, Nyctibatrachus deccanensis, Nyctibatrachus major and Nyctibatrachus sanctipalustris). The taxonomic revision and description of new species is based on new morphological, behavioural, ecological and molecular data from available type specimens and/or recent collections from throughout the distribution range of Nyctibatrachus. Specimens from the type localities of all previously described species were collected and discussed along with the type specimens. Nyctibatrachus sholai is considered a junior subjective synonym of N. deccanensis. Nyctibatrachus sanctipalustris modestus is resurrected from synonymy, but allocated to the genus Fejervarya. A new gland, the subocular gland is introduced to anuran morphological terminology. Both the courtship behaviour and ovipositional sites of four species are described for the first time. The process of fertilisation was carried out in the absence of physical contact between males and females in all four species. Furthermore, previously unreported parental care behaviour is documented for the genus, including biparental egg attendance (probably clutch hydration) and egg guarding (active predator defense). A brief outline of tadpole development from egg to metamorph is provided for Nyctibatrachus aliciae, with figures of the major developmental stages.